Asymmetric information of variance risk premium in the Chinese market: upside and downside volatility spillovers - Jue Gong; Gang-Jin Wang; Zhao-Chen Li; Gazi Salah Uddin (Management System Engineering)
Abstract We investigate the degree of asymmetry in the variance risk premium (VRP) using SSE 50 ETF options in the Chinese market. Our approach decomposes the VRP into upside and downside components and quantifies the dynamic spillover asymmetry measure (SAM). This innovative methodology enables us to explore the asymmetric volatility information embedded in VRP, offering valuable insights into investor sentiments and risk perception. By analyzing the volatility spillovers of semi-VRP, we observe that downside VRP exhibits more pronounced fluctuations compared to upside VRP, indicating that risk aversion sentiments intensify during market downturns and exert a greater influence on market risk levels. Additionally, the dynamics of SAM reveal that upside and downside VRP alternately dominate in shaping market volatility, reflecting the time-varying nature of asymmetric risk transmission. Unexpected risky events, such as policy announcements or market crises, emerge as potential drivers that amplify these asymmetries, prompting shifts in investor sentiment and market behavior. These findings contribute to a deeper understanding of the role of asymmetric VRP in financial markets, emphasizing its critical impact on volatility dynamics and the broader market sentiment transition, particularly in the context of emerging markets like China.